(untitled) (ETNOSIA : Jurnal Etnografi Indonesia, 2017)
Local cultural symbols have been used massively along with the spirit of primardialism, subtituting javaneseness nationalism of the New Order. This article aims to examine Bugis cultural values and the shift of meaning used as the preference in the political practice that support power relations. To the present, in the era of local autonomy, the old order has reborn in Buginese culture and force the cultural legitimacy, such as reproduced values and eve more related the political practices and power struggles. Such tendency has resulted in the division of Belawa community into two groups those who geneologically have political power (anakarung) and those who have not. This has formed a patronage stucture relationship based on delicate agreement (assituruseng). Such a values has cultural legacy which is then reproduced as an instrument in the political practice and maintain power domination by anakarung. Such a strategy is a hegemonic effort, utilizing various components of Bugis cultural through symbols and adages.